2010
DOI: 10.1177/0961203310370043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of predialysis comorbidity and damage accrual on mortality in lupus patients treated with peritoneal dialysis

Abstract: The predialysis CCI, instead of SDI, determines an increased risk for mortality in lupus patients treated with PD. The prognosis of lupus patients treated with PD largely depends on the severity of predialysis comorbidity, especially cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…34 Similarly, pre-dialysis comorbid illnesses as determined by the CCI, but not increased severity of pre-dialysis damage accrual, predicts all-cause mortality in lupus patients treated with peritoneal dialysis. 35 Comorbidity as a predictor for mortality and hospital LOS had also been reported in patients with cancer, 36 patients with acute burn injury, 37 patients with cirrhosis, 25 patients with sepsis, 38 critically ill patients in the ICU, 16 and a general hospital population. 20 It is well known that death is rarely due to uncontrolled lupus episodes but rather attributable to side effects of treatments in the late course of SLE.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…34 Similarly, pre-dialysis comorbid illnesses as determined by the CCI, but not increased severity of pre-dialysis damage accrual, predicts all-cause mortality in lupus patients treated with peritoneal dialysis. 35 Comorbidity as a predictor for mortality and hospital LOS had also been reported in patients with cancer, 36 patients with acute burn injury, 37 patients with cirrhosis, 25 patients with sepsis, 38 critically ill patients in the ICU, 16 and a general hospital population. 20 It is well known that death is rarely due to uncontrolled lupus episodes but rather attributable to side effects of treatments in the late course of SLE.…”
Section: Discussionmentioning
confidence: 95%
“…20 It is well known that death is rarely due to uncontrolled lupus episodes but rather attributable to side effects of treatments in the late course of SLE. 35 This association showed a possible synergy between the effects of SLE and comorbidity, which suggests that treatment of comorbidities should be considered an integral part of clinical care for patients with SLE. Successful treatment of comorbidity would reduce the mortality attributable to comorbidity itself, and perhaps also the mortality attributable to the synergy between comorbidity and SLE.…”
Section: Discussionmentioning
confidence: 98%
“…Lupus patients with recurrent infections, malignancies, or other pre-existing comorbidities may be poor candidates for PD or pre-emptive transplantation due to increased complication rates 7, 9, 10 . A recent survival analysis of LN ESRD undergoing PD revealed that pre-dialysis SLE activity scores had limited prognostic value but preexisting comorbidities, especially cardiovascular conditions, were associated with significantly higher mortality rates among SLE PD patients 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether long-term outcomes among LN ESRD patients differ according to the kidney replacement option chosen, in particular the two dialysis modalities 68 . Although there is a paucity of prospective data comparing infection rates among LN ESRD patients receiving HD compared to PD, a few studies have suggested an increased risk for peritonitis and higher mortality rates among SLE patients receiving PD 7, 9, 10 . Past studies of the influence of dialysis modality upon SLE disease activity have also yielded inconsistent results 7–13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation